Ornamental Potential of Gentiana kurroo Could be a Boon for its Survival: A Critically Endangered Species - Srivastava, Amber; Singh, Harminder; Bhandari, Aakriti; Kumar, Puneet; Panwar, G. S.; Mao, A. A. (Indian Forester, 2022)
No Abstract.